Pengaruh E-Commerce, Sistem Informasi Akuntansi, dan Kompetensi Sumber Daya Manusia Terhadap Kinerja Keuangan UMKM Di Kota Denpasar - Again, Ni Luhtu Aprilia; Putra, Cokorda Gde Bayu; Hutnaleontina, Putu Nuniek (UNHI Press, 2025)
The study aims to empirically analyze the influence of e-commerce, accounting information systems and human resources (HR) on the financial performance of micro, small and medium enterprises (MSMEs) in Denpasar City. In determining the sample,the researdh used the Slovin formula with the results obtained by a total of 100 MSMEs with a sampling method, namely probability random sampling using stratified random sampling. The data analysis technique used is partial least square-based structural equation model. The results of the study show that e-commerce, variabels, accounting information systems and human resources (HR) have a significant positive influence on business financial performance.